2019
DOI: 10.1038/s41588-018-0322-6
|View full text |Cite
|
Sign up to set email alerts
|

GARFIELD classifies disease-relevant genomic features through integration of functional annotations with association signals

Abstract: Loci discovered by genome-wide association studies (GWAS) predominantly map outside protein-coding genes. The interpretation of the functional consequences of non-coding variants can be greatly enhanced by catalogues of regulatory genomic regions in cell lines and primary tissues. However, robust and readily applicable methods to systematically evaluate the contribution of these regions to genetic variation implicated in diseases or quantitative traits are still lacking. Here we propose a novel approach that l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
175
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(188 citation statements)
references
References 37 publications
(70 reference statements)
8
175
0
Order By: Relevance
“…Using a two-step conditional analysis (Methods), PHA-stimulated T cells had the largest number of eGenes (6.3%; Table S5) with multiple independent eQTL signals. GARFIELD enrichment analysis 24 showed that the cis-eSNPs were enriched in 3' untranslated regions (UTR), 5' UTR, and exon regions ( Figure S2), consistent with known mechanisms of cis-eQTLs.…”
Section: Genetics Of Neonatal Gene Expression In Innate and Adaptive supporting
confidence: 58%
See 1 more Smart Citation
“…Using a two-step conditional analysis (Methods), PHA-stimulated T cells had the largest number of eGenes (6.3%; Table S5) with multiple independent eQTL signals. GARFIELD enrichment analysis 24 showed that the cis-eSNPs were enriched in 3' untranslated regions (UTR), 5' UTR, and exon regions ( Figure S2), consistent with known mechanisms of cis-eQTLs.…”
Section: Genetics Of Neonatal Gene Expression In Innate and Adaptive supporting
confidence: 58%
“…We performed enrichment analyses using GARFIELD (version 2) to investigate the enrichment patterns of cis-eQTLs using predefined features ("annotation data") such as genic annotations from ENCODE, GENCODE, and Roadmap Epigenomics project provided by this tool 24 . GARFIELD evaluates enrichment using generalised linear regression models that account for allele frequency, distance to the nearest gene TSS, and LD.…”
Section: Enrichment Analysismentioning
confidence: 99%
“…We analysed all genetic variants of these association results for enrichment in regulatory and functional annotations, using GARFIELD. 46 GARFIELD accounts for LD structure and local gene density and derives the statistical significance of the functional enrichment (odds ratios) by fitting a logistic regression model. The strongest associations of the genetic loci were to open-chromatin regions in fetal heart tissue, particularly in the mid and apical regions ( Figure 3, Figure 14 in the Supplement).…”
Section: Functional and Molecular Associations Of The Discovered Locimentioning
confidence: 99%
“…We used GARFIELD version 2 46 for functional enrichment analyses of genetic variants with multi-trait GWAS p-value < 10 −6 . The GARFIELD software package and pre-computed data for samples of Caucasian ancestry (LD and annotation data, minor allele frequencies of genetic variants and their distances to nearest transcription start site) were downloaded from https://www.ebi.ac.uk/birney-srv/GARFIELD.…”
Section: Functional Enrichment Analysismentioning
confidence: 99%
“…These findings implicate ncRNAs in the mechanisms driving complex traits. GWAS has allowed inference of trait-relevant 10 tissues or cell-types (Finucane et al, 2015(Finucane et al, , 2018, biological pathways (Iotchkova et al, 2019;Lamparter et al, 2016), and therapeutic drugs (Terao et al, 2016); therefore, determining the influence of non-coding causal variants from GWAS on ncRNA expression in relevant cell-types is a promising approach to deepen our understanding of complex trait mechanisms ( Figure 1A). For mRNAs, such analyses have already 15 improved understanding of the genetic architecture of complex traits; mRNA expression quantitative trait loci (eQTL) information, resolved to the tissue-or cell-type-level, has been linked to GWAS results to implicate the cell types and tissues involved in complex traits (Ardlie et al, 2015;Ishigaki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%